Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1292/jvms.62.677
|View full text |Cite
|
Sign up to set email alerts
|

Chaaracteristics of Foot and Mouth Disease Virus in Taiwan.

Abstract: ABSTRACT. Since March 1997 two strains of foot and mouth disease (FMD) virus have found their way into Taiwan, causing severe outbreaks in pigs and in Chinese yellow cattle. Outbreaks occurred in March 1997 were caused by a pig-adapted virus strain (O/Taiwan/ 97) which did not infect other species of cloven-hoofed animals by natural route. The epidemic spread over the whole region of Taiwan within two months and the aftermath was 6,147 pig farms infected and 3,850,746 pigs destroyed. In June 1999, the second s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…The role of the 3A protein in viral virulence was demonstrated during studies of the FMDV isolate responsible for an outbreak in Taiwan in 1997 (designated O/Taw/97) (see below). This outbreak was unusual in that only pigs, and not cattle, were affected, and the disease had an unusually high mortality rate in pigs (143,216). Molecular characterization of the virus revealed that it contained a 10-codon deletion in the C-terminal half of the 3A protein (47).…”
Section: Virulence Factorsmentioning
confidence: 98%
“…The role of the 3A protein in viral virulence was demonstrated during studies of the FMDV isolate responsible for an outbreak in Taiwan in 1997 (designated O/Taw/97) (see below). This outbreak was unusual in that only pigs, and not cattle, were affected, and the disease had an unusually high mortality rate in pigs (143,216). Molecular characterization of the virus revealed that it contained a 10-codon deletion in the C-terminal half of the 3A protein (47).…”
Section: Virulence Factorsmentioning
confidence: 98%
“…It was suggested that subclinically infected sheep were a major risk factor in the transmission and spread of FMD both within and between countries during the pandemic. It was suggested that the origin of the Pan Asia strain of ME-SA topotype which caused recent FMD outbreaks in Taiwan, Japan, and Mongolia would be viruses circulated in Mainland China [4,5,11,14]. It was believed that there was widespread FMD in China such as Beijing, Shenyang, Jilin, and Heilongjiang Provinces during the winter season from 1999 to 2000.…”
Section: Surveillance Of Fmdmentioning
confidence: 99%
“…According to an inspection program conducted by the Council of Agriculture in 2004, illegal slaughter of pigs dying of unidentified diseases and sale of the pork at a reduced price were common in Taiwan and probably were associated with transmission of the organism ( 4 ). In Taiwan during 1996–1997, a large epidemic of swine foot-and-mouth disease occurred ( 5 ), and consumption of pork decreased substantially. To prevent further spread of that epidemic, the government implemented massive slaughter of infected pigs and a swine vaccination policy ( 5 ).…”
mentioning
confidence: 99%
“…In Taiwan during 1996–1997, a large epidemic of swine foot-and-mouth disease occurred ( 5 ), and consumption of pork decreased substantially. To prevent further spread of that epidemic, the government implemented massive slaughter of infected pigs and a swine vaccination policy ( 5 ). Coincidently, in 1996–1998, S. enterica Choleraesuis infections among humans decreased significantly (p<0.001) ( 2 ).…”
mentioning
confidence: 99%